The tutktuks in Maadi: What is their presence disrupting? - Kaddah, Doaa Ayman (AUC Knowledge Fountain, 2017)
Why is the maneuvering of the tuktuks in certain elite spaces in Maadi a disruption to the fragile and in many ways, imaginary boundaries between people, spaces, objects, histories and narratives? How can one street, whether it is the one where I live or Street 9 where I did my fieldwork, encompass a wide range of lives and worlds that do not "touch"? Why is it ok for the tuktuk to be seen in Arab El Maadi, usually conceived as a lower-class neighborhood adjacent to Sarayat El- Maadi, but when it moves in Sarayat El-Sarayat, it becomes a disruption to the senses? Why is the tuktuk in motion contested in some areas, and what happens when it stays still in others? How do the elites of Maadi justify the exclusion of the tuktuk from their elite spaces?How deep does the pool of their common sense goes? Is there a history to this pool? If so, how much are the dead still alive and in what ways are they summoned back? In this thesis, I answer these questions through an ethnography of storytelling of the life worlds I encountered. My ethnographic research on the tuktuks in Maadi as well as the peoples steering them is productive in affectively encountering Maadi's social geographies of power. Their "disruptive" and "controversial" mobility in elite spaces in Maadi sheds light on how social divides that are not physically constructed as walls, yet are invisible palpable barriers signify the social and historical segregation of Maadi.